Mengolah Limbah Rumah Tangga Di Desa Randugunting Kecamatan Bergas Menjadi Pupuk Organik Cair - Alfa Faridh Suni; Dian Nadia Mauretha; Achmad Setiyo Wibowo (Universitas Negeri Semarang, 2026)
The socialization of making Pupuk Organic Cair (POC) in Randugunting Village is an effort to deal with the abundance of household organic waste. This outreach aims to utilize household organic waste such as wilted vegetables. This household organic waste rots very quickly and carries many diseases if left untreated. Therefore, this waste is processed into fertilizer which is useful for the residents around Randugunting Village. The socialization methods used are training and direct practice. The community service’s results revealed that Pupuk Organik Cair produced had sufficient nutritional content, including nitrogen, phosphorus and potassium, which are essential for plant growth. After the socialization is complete, the result are used to water the village's TOGA. Thus, the manufacture of Pupuk Organik Cair in Randugunting Village provides direct benefits for residents through increasing TOGA yields, while supporting more environmentally friendly and sustainable agricultural practices.